Genetic control of nucleolar size: An evolutionary perspective. (25th April 2016) - Ma, Tian-Hsiang; Lee, Li-Wei; Lee, Chi-Chang; Yi, Yung-Hsiang; Chan, Shih-Peng; Tan, Bertrand Chin-Ming; Lo, Szecheng J.
ABSTRACT: Exploiting a C. elegans mutant ( ncl-1 ) exhibiting nucleolar abnormalities, we recently identified the let-7 / ncl-1 / fib-1 genetic cascade underlying proper rRNA abundance and nucleolar size. These 3 factors, let-7 (a miRNA), NCL-1 (a member of the TRIM-NHL family), and fibrillarin (a nucleolar methyltransferase), are evolutionarily conserved across metazoans. In this article, we provide several lines of bioinformatic evidence showing that human and Drosophila homologues of C. elegans NCL-1, TRIM-71 and Brat, respectively, likely act as translational suppressors of fibrillarin. Moreover, since their 3′-UTRs contain putative target sites, they may also be under the control of the let-7 miRNA. We hypothesize that let-7, TRIM and fibrillarin contribute activities in concert, and constitute a conserved network controlling nucleolar size in eukaryotes. We provide an in-depth literature review of various molecular pathways, including the let-7 / ncl-1 / fib-1 genetic cascade, implicated in the regulation of nucleolar size.